PENGELOLAAN DAN PEMASARAN BANK SAMPAH RW 17 CIMEKAR UNTUK PENINGKATAN LINGKUNGAN DAN EKONOMI - Wahyuni, Sri; Hidayat, Dadang Saeful (Jurnal Abdimas Sang Buana, 2025)
The main issue faced by the residents of RW 17, Cimekar Village is the low level of environmental awareness and the suboptimal management of waste that could otherwise have economic value. This community service activity aims to enhance the community’s capacity to manage and market the outputs of the KAPPSA Waste Bank sustainably, thereby promoting behavioral change towards the environment while providing economic benefits. The method used was a participatory approach through training, mentoring, and joint evaluations involving residents, waste bank administrators, and local community leaders. The activities focused on educating the community about household waste management, sorting, collection, recordkeeping, and marketing strategies for recyclable and sellable waste. The results showed an increase in the community’s understanding of proper waste management and active participation in waste bank activities. Furthermore, the waste bank administrators began implementing basic recordkeeping and marketing systems that helped increase income from waste sales. The conclusion of this activity is that participatory waste bank management and marketing can improve environmental awareness while adding economic value for the community, thus supporting the realization of a clean and sustainable environment.